Intentions of punitive penalties (Journal of Human Sciences, 2022)
Punishment penalties are an important part of the Islamic criminal system, and they are punishments for sins and disobedience for which it was not prescribed specific and unquantifiable penalties, Rather, the matter of its determination is left to the guardAian or his representative, provided that those penalties are in accordance with the rules The spirit of Sharia, its purposes, goals and objectives from punishments in general and punishments in particular, and punitive punishments differ from the rest of the punishments in Islamic legislation in several respects, such as their difference from the punishments crimes and the crimes of retribution, blood money and expiations And all other capabilities, and punishments are types and categories according to the nature of the crime, the offender’s condition, the circumstances of the crime, and so on. It is also a matter of disagreement among the jurists on how to estimate it and the type of punishment, but what is important in this is linking the punishments to punitiveness With the purposes of Sharia and proving the intentions of punitive penalties, and that they are not devoid of judgment, secrets, goals and objectives; when and has achieved one of the purposes of Sharia in terms of punishment or an interest that was required and desirable, but it must as such Punishments are commensurate with the guilt or offense committed or the offense or the disobedience,  So that excuses are not unjust, unjust and transgressive, as Punishments are required to achieve, even partially, reprimand and deterrence, and to bring benefit or repel corruption. Excuses are prescribed for discipline. It is not for torture, if the guardian or his representative thinks that it will be useless or devoid of any benefit or interest in the matter. If there were no excuses, and this situation is neither required nor desirable, and vice versa.